PENGARUH KEDISIPLINAN BELAJAR, MANAJEMEN WAKTU, DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR PADA MAHASISWA REGULER SORE DAN EKSTENSI SELAMA PEMBELAJARAN HYBRID LEARNING (Studi Pada Mahasiswa STIE Indonesia Banking School)” - Humaira , Nadira; Bagasworo , Wasi (Ibs Press, 2024)
This study aims to test and analyze the influence of learning discipline, time management, and learning motivation on learning outcomes in regular afternoon and extension students during hybrid learning at STIE Indonesia Banking School students during the 2020 to 2023 learning period. In this study, there are independent variables, namely learning discipline, time management, and learning motivation. While the dependent variable in this study is learning outcomes.Hypothesis testing in this study used the PLS or partial least square method with SmartPLS 3.0 software. The data collection technique used a Google Form application questionnaire to collect all information from the respondents. The sample in this study were active students of STIE Indonesia Banking School class of 2020-2023 who participated in hybrid learning.The results of the analysis show that learning discipline has a positive and significant effect on learning outcomes. Time management shows that it has no effect on learning outcomes. Learning motivation has a positive effect on learning outcomes.